Feasibility of near Infrared Chemical Imaging for Pharmaceutical Cleaning Verification. Issue 3 (June 2013) - Alvarez-Jubete, Laura; Mishra, Jaya; Jones, Ian; Cullen, Patrick J.; Sullivan, Carl
In conformity with the 2011 Food and Drug Administration guidance for industry, Process Validation: General Principles and Practices, there is a requirement for new methodologies that support continued cleaning verification of manufacturing equipment. Near infrared chemical imaging (NIR-CI) represents an attractive alternative to the current methodologies for cleaning verification since it represents a direct, rapid and sensitive technology. The aim of this study was to test the feasibility of NIR-CI for cleaning verification. Stainless steel, glass and Perspex surfaces were soiled with selected active pharmaceutical ingredients (APIs) with the resulting hyperspectral data employed to identify and quantify the dried residues. Correlations to high-performance liquid chromatography (HPLC) swab analysis were also made. Linear models were obtained for the number of API classified pixels and applied soil concentration with R 2 values of 0.90 and 0.98 for caffeine and sulfathiazole sodium salt, respectively, on stainless steel coupons. In the case of caffeine soils on borosilicate glass and Perspex coupons, the obtained R 2 values were 0.95 and 0.96, respectively. These R 2 values suggest a linear relationship between the number of API classified pixels and applied soil concentration. The calculated detection limits for caffeine and sulfathiazole sodium salt soils on stainless steel coupons were 48 μg and 18 μg 50 mm −2, respectively. For caffeine soils on borosilicate glass and Perspex coupons the calculated detection limits were 33 μg and 27 μg 50 mm −2, respectively. However, visual inspection of the NIR-CI following the classification function point to limits of detection closer to 1 μg 50 mm −2 or lower. High correlations ( R 2 of 0.91 and 0.93 for caffeine and sulfathiazole sodium salt, respectively) were also obtained between NIR-CI API soil quantification and swabbing/HPLC analysis. This research points to possible future use of portable CI systems for continued cleaning verification of pharmaceutical residues.